Design approach for wideband FM receiver using RTL-SDR and raspberry PI - Satya Narayana, P; N.V.S. Syam Kumar, M; Keerthi Kishan, A; V.R.K. Suraj, K (International Journal of Engineering and Technology, 2018)
Software defined radio replaced majority of hardware modules like mixers, filters, modulators and demodulators etc., with Software blocks in the field of radio electronics and communication. In this some or all the functionalities are Configurable using this software implemented on technologies like FPGAs, DSPs etc. Owing to lack of ease in implementing and reconfiguring huge hardware modules, we move on to implement an adaptable communication system with the help of SDR, as it can be easily configured to work with wide range of frequencies. We find various SDR transceiver modules which can be interfaced with digital computer and aided with firmware like GNU radio, SDR shark, etc., allowing us to construct blocks with the help of built in components that decode and process the received data and produce required output. In requirement of implementing a cost-effective, compact sized and portable system, we use a processing unit providing enough computational power to perform signal processing tasks which is Raspberry pi. Here we are going to implement a low cost SDR communication system that capture, process and visualize the Wide Band Frequency signal.Â